(untitled) (Current Horticulture, 2024)
The study was carried out to evaluate variability between different ber (Ziziphus mauritiana Lamk.) germplasm on the basis of flowering and fruit setting. Significant variability was observed for the recorded parameters. Bawal Ber 12 exhibited early initiation, while BS 3 showed delayed flower initiation. The shortest flowering duration was recorded in Bawal Ber 9 (37 days), whereas longest flowering duration was recorded in Bawal Ber 1, Bawal Ber 5 and BS 1 (42 days). Different germplasm displayed notable variation in mature fruit colour, including greenish-yellow, yellow and green. Oval shaped fruits were observed in Bawal Ber 1, Bawal Ber 9 and BS 3 while Bawal Ber 2, Bawal Ber 5, Bawal Ber 6, Bawal Ber 7, Bawal Ber 8, Bawal Ber 10 and BS 2 exhibited ovate shape. Bawal Ber 3, Bawal Ber 4 and BS 1 had oblong fruits and Bawal Ber 11 displayed an oblate shape whereas Bawal Ber 12 had round fruits. The stone shape of ber germplasm varied with some exhibiting a spindle, oblong, club or oval shape. Bawal Ber 1, Bawal Ber 2, Bawal Ber 3, Bawal Ber 4, Bawal Ber 5, Bawal Ber 7, Bawal Ber 9, Bawal Ber 10 and Bawal Ber 12 had a plain fruit surface, while Bawal Ber 6, Bawal Ber 8, Bawal Ber 11, BS 1, BS 2 and BS 3 showed a ridged and wart fruit surface.